The roles of psychological needs satisfaction and impulsivity to parent-child conflict and non-suicidal self-injury - Chang Wei; Bao Liu; Yu Wang; Yaping Wang; Qian Xu (Frontiers in Psychiatry)
IntroductionNon-suicidal self-injury is a serious health problem among adolescents. However, the association between parent–child conflict and adolescent non-suicidal self-injury and its underlying mechanisms have not been studied sufficiently. Based on the interpersonal model of non-suicidal self-injury, we tested the relationship between parent–child conflict and adolescent non-suicidal self-injury. Furthermore, based on self-determination theory and the diathesis-stress model, we examined whether psychological needs satisfaction mediated the link between parent–child conflict and adolescent non-suicidal self-injury, and if impulsivity moderated this mediating effect.MethodsUsing cross-sectional design, we recruited 656 adolescents (Mage = 13.43; 47% female) from two junior high schools in the Hubei province of China.ResultsThe results indicated a positive association between parent–child conflict and adolescent non-suicidal self-injury. Psychological needs satisfaction mediated the relationship between parent–child conflict and adolescent non-suicidal self-injury. High impulsivity strengthened the indirect effect of parent–child conflict on adolescent non-suicidal self-injury. Specifically, high impulsivity strengthened the direct relationship between psychological needs satisfaction and adolescent non-suicidal self-injury and further strengthened the indirect association between parent–child conflict and adolescent non-suicidal self-injury.ConclusionsOur findings highlight the potential mechanisms underlining the relationship between parent–child conflict and adolescent non-suicidal self-injury. Our findings can inspire educational practitioners to focus on the interaction of family risk factors and individual risk factors when developing intervention programs for adolescent non-suicidal self-injury.